From fear to facts: a multi-channel approach to information seeking amid influenza-like illness outbreaks - Qi, Shenghao; Tham, Jen Sern; Waheed, Moniza; Hashim, Norliana (Frontiers in Public Health, 2025)
BackgroundDuring recurrent large-scale influenza-like illness (ILI) crises, the factors influencing the information-seeking intentions of Chinese individuals across multiple channels during crises remain underexplored.ObjectiveGuided by the risk information seeking and processing (RISP) model, this study proposes a modified RISP model to comprehensively analyze information-seeking intentions through the lens of risk communication.MethodsTo empirically validate the proposed research model, we conducted an online cross-sectional survey with 2,604 Chinese citizens aged 18 years and older. Structural equation modeling (SEM) and ordinary least squares regression analysis were employed to analyze the survey data.ResultsOur findings revealed that during ILI crises, Chinese individuals experienced a spectrum of emotions; as perceived risk increased, negative emotions intensified while positive emotions decreased. Increased negative emotions correlated with a greater sense of information insufficiency, whereas heightened positive emotions correlated with a reduced perception of it. Consequently, Chinese individuals facing information deficiencies were more inclined to seek information from diverse sources, including interpersonal sources, traditional media, search engines, and social media. Moreover, statistical analysis indicated that stronger beliefs in channel complementary strengthened the relationship between information insufficiency and information-seeking intention across multiple channels (access to medical expertise belief, tailorability belief, convenience belief, anonymity belief).ConclusionThis study outlines a pathway for advancing the RISP model and offers practical strategies for effective risk communication to mitigate risks and enhance public perception and behavior. It also discusses implications for health communication, promotion, and behavior change.